Structural and functional characterization of a metaloprotease of the venom of Bothrops roedingeri by proteomic approach - Juan Carlos Campos Gonzales (2019)
The species belonging to the genus Bothrops are very important in the field of research for possessing proteolytic enzymes, which has as main characteristics to have a varied biological action and contribute to disorders in coagulation, necrosis and hemorrhage formation therefore a modern platform is needed in the study of these enzymes to be able to suggest an updated methodological model in the study of all the proteins expressed by a biological system that allows us to know the current status of the species, as well as to use this information in the biotechnological construction of information with possible future therapeutic purposes. The first objective is to purify and characterize one of the proteolytic enzymes present in the venom, such as metalloprotease, for which we initially worked with Hydrophobic Interaction chromatography with columns from the HITrap system, which resulted in the presence of 6 peaks, being peak 2 that showed hemorrhagic activity being called HFBr, with this obtained fraction SDS PAGE electrophoresis was performed in reductive condition using DTT that showed a molecular mass of 23 kDa and in a non-reducing condition a mass of ~ 27 kDa. , for the determination of the intact mass of the poison we resorted to the method of Mass Spectrometry obtaining our raw and intact results by Electrospray (ESI) giving a result of 27342.6641 Da. A characterization of the primary structure of "novo" was carried out by tryptic hydrolysis (MALDI / TOF), obtaining 6 amino acid sequences to subsequently carry out a Bioinformatic analysis through the SWISS-PROT database to then carry out a sequential homology analysis with Use of the DNAStar Software specifying that the protein studied is a Metalloprotease of the Bleeding family. Finally, tests were done for their biological characterization to determine the hemorrhagic activity with a method of intradermal inoculation in mice obtaining the values of induced hemorrhage of Bothrops roedingeri corresponding to 9.5 mm ± 0.15 mm for the total venom and 8 ± 0.12 mm for the fraction HFBr, respectively.